Heteropic Pancreatic Rest in Gall Bladder: Is It Really Worrisome? - Sameer Ahmed Abdul Hamid Ansari; Khalid Ahmed Alsindi; Husham Bakry (Archives of Medicine and Health Sciences)
Heterotopia of pancreas is defined as an abnormal location of pancreatic tissue devoid of vascular and anatomical connections from main pancreas. The stomach is the most common site of such heterotopia, although the lesion can be encountered throughout the entire gastrointestinal tract. Involvement of gallbladder is extremely rare with few cases reported so far in the literature. We described a similar finding in a 28-year-old female patient, who presented with chronic abdominal pain.